2014
DOI: 10.17659/01.2014.0085
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Intussusception with Malrotation and Meckel’s Diverticulum

Abstract: Abstract:The cause of intussusception in most infant is unclear. Intestinal malrotation has been postulated as a possible cause in some infants. The reported case is unusual not only in respect of malrotation associated with intussusception but also because of the presence of mesenteric adenitis and Meckel's diverticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The exact aetiology is still unknown and almost 81% of the cases are idiopathic. 3 Various conditions have been found to be associated with it. 4 Adenovirus infection 5 as well as vaccination against rota virus have been proposed to increase the risk of intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…The exact aetiology is still unknown and almost 81% of the cases are idiopathic. 3 Various conditions have been found to be associated with it. 4 Adenovirus infection 5 as well as vaccination against rota virus have been proposed to increase the risk of intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the barium enema shows a classic image of a "coiled spring" with obstacle to the contrast product at the level of the invagination and localization of the coecum. In 80 to 87% of Waugh Syndrome cases proven surgically the barium enema was abnormal (Singh, A. P. et al, 2015). The abnormal rotation has a variety of clinical presentations, ranging from abdominal pain to acute midgut volvulus with ischemic bowel injury.…”
Section: Figure 1: Hydrostatic Reductionmentioning
confidence: 99%
“…Intussusception is one of the common causes of intestinal obstruction in pediatric population and is mostly (81%) idiopathic. 1 Secondary intussusception occurs due to a variety of etiological factors such as Meckel's diverticulum, hypertrophied Peyer's patches, congenital bands, and intestinal lymphomas. 1 The rare association of intestinal malrotation in conjunction with intussusception was first described by George E Waugh in 1911.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Secondary intussusception occurs due to a variety of etiological factors such as Meckel's diverticulum, hypertrophied Peyer's patches, congenital bands, and intestinal lymphomas. 1 The rare association of intestinal malrotation in conjunction with intussusception was first described by George E Waugh in 1911. It was termed Waugh's syndrome (WS) by Brereton et al after a prospective study confirmed this rare association.…”
Section: Introductionmentioning
confidence: 99%